THE STATE AND THE SPORT: TWO MOVEMENTS, TWO RELATIONS (Fiep Bulletin - online, 2014)
Before was restrict to the spheres in practice and social representations about its function, the sportive phenomenon in the contemporary is having the investigation expand, becoming study object, when they extend its observation sphere, approximated to others discussions  as those relatives to the communication areas, marketing, administration  and fundamentally to our case, the politic area. That way, this article has for objective analyses, in the contemporary politic theory, the actuation of the Brazilian state in the elaboration, systematization, implementation and offers in the public politics about sport and leisure in two movements, the first, before the constitution promulgation in 1988, time that the offers the politics in this area was work and prior of the national government; and the second, after constitution, when we had these politics transfer to the cities. At the first moment, the politics about leisure and sport had a general profile, universe; follow the orientation of other government politics. At the second moment, we had the politics inclination to the particularities in the social groups. The logic of the politics in the cities was in see this prerogative that passed to exist in Brazilian society. In a general form, the cities still need an administrative and physics infrastructure, capable in develops satisfactory the principal functions in leisure and sport politics, to propitiate the equality in opportunities to the sport and leisure to all cities. Almost always the politics irregular discontinue and only to the elections, without any other worried with aspects relative to see the specifities and promoting the equality in the rights and opportunities.
Keywords: sport-state; public politics; politics in the cities